Determinants of Audit Fee in Chinese Market: An empirical study - KE, RUNFENG/R (2013)
Since 2001, audit fee started to be disclosed in China. This paper investigates the determinants of audit fees in Shenzhen Stock Exchange using the publicly available resources. A set of sample formed by the financial data and audit information of all A share listed companies in Shenzhen Stock Exchange during 2007-2011 is used in this research, Random effect regression and fixed effect regression are both used in this study. Six aspects of determinants are tested in the model, which are auditor size, size of audit client, complexity of audit client, profitability of audit client, audit risk and time variable. Different determinants of audit fees in different industries are investigated in this paper. Results of both regression models in each industry are detailed described and analyzed in the paper. The results from random effect regression model are accepted as the final result of this study, which exhibits that auditor size, size of audit client and profitability of audit client are significant determinants of audit fees.